Optimasi Waktu Pengantaran Barang melalui Model Penugasan Kurir dengan Metode Hungarian Termodifikasi pada Data Tidak Seimbang - Riskiani, Riskiani; Busrah, Zulfiqar (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2026)
This study aims to apply the Hungarian method to the assignment problem in determining the allocation of couriers in the case of delivering goods at PT. Shopee Express Soreang Kota Parepare Hub. The Hungarian method is used to determine the optimal allocation of couriers based on the efficiency of the delivery time of goods so that the total distribution time can be minimized. In its implementation, adjustments were made to the procedures of the Hungarian method to accommodate unbalanced data conditions. Validation of assignment results is carried out using Program for Operations Management-Quantitative Methods (POM-QM) software for Windows to ensure that the solutions obtained through manual calculations match the system's computational results and actually produce optimal values. The results showed that the total average delivery time before optimization of 53.45 minutes could be reduced to 41.80 minutes after the application of the Hungarian method, resulting in a time efficiency of 11.65 minutes. Validation using POM-QM for Windows shows results consistent with manual calculations. Thus, the Hungarian method has proven to be effective in improving the efficiency of courier assignments and minimizing the delivery time of goods.